State-dependent RF-Dressed Ring traps for Sagnac Interferometry - Atkocius, Vilius (2024)
This thesis describes the experimental realisation of state-dependent traps employing RF-dressed adiabatic potentials. Rb-87 atoms have been successfully confined to chip-based atom traps that can independently address atomic ground states defined by the total angular momentum, F. The ring-shaped trap can be used as a Sagnac interferometer to measure rotation with respect to the inertial frame of reference. The results of spatially dependent radio frequency field polarisation control in this trap resulted in counterpropagating motion of the atoms in the F = 1 and F = 2 states.